Current state of natural ecosystems of Western Tanirtau (Tien Shan) and taxonomical structures of the region’s dendroflora - Sikhymbayev, A. Y.; Aralbay, N. K.; Sikhimbayeva, S. M.; Mamykova, R. U.; Zhgitekov, T. A.; Narbota, B. E. (International Journal of Biology and Chemistry, 2019)
Special reports on the Western Tanirtau dendroflora are currently absent. The essence of the floristic analysis given in this paper is identification of taxonomical structure of the Western Tanirtau dendroflora at the level of superfamily groups, families and genera. The objectives of the study are identification of the current state of natural ecosystems in the region. The study of the Western Tanirtau dendroflora was conducted from 2008 to 2017. The study was conducted in the region of the Kazakh part of the Western Tanirtau in the south of Kazakhstan. Collection and processing of materials was carried out by the method of A.K. Skvortsov. All species of hardy-shrub plants observed on all mountain altitudinal belts, including ranges, gorges and anthropogenically-urbanized ecosystems were recorded. During the analysis of the materials collected in the Western Tanirtau territory and review of previously collected materials identified 396 taxa of dendroflora belonging to 130 genera and 50 families. The proposed material is actual reflection of the current state of the Western Tanirtau dendroflora within Kazakhstan and for the first time a floristic spectrum of hardy-shrub plants was developed at the modern level of taxonomy and nomenclature. For the first time, the most complete list of the Western Tanirtau dendroflora, numbering 396 species of the hardy-shrub plants, is given. The data of the conducted researches testify that the Western Tanirtau dendroflora is a large center for enrichment of the genofond of plants in Kazakhstan. The complete list of the species is recommended for use in the compilation of the Plant Identifier in the vicinity of Shymkent city, as well as in the theoretical analysis of the Western Tanirtau flora. In addition, the results of the study are proposed for use in the development of resource and environmental activities in the region.